2016
DOI: 10.3855/jidc.6925
|View full text |Cite
|
Sign up to set email alerts
|

Middle East respiratory syndrome coronavirus (MERS-CoV) outbreak perceptions of risk and stress evaluation in nurses

Abstract: Introduction: Saudi Arabia was affected by an outbreak of Middle East respiratory syndrome coronavirus (MERS-CoV). We aimed to determine the perception of risk and level of stress among nurses. Methodology: A questionnaire survey was administered to determine the perceptions of risk of MERS-CoV infection. Results: The majority of the participants were females (332; 86.0%), and there were 54 (14.0%) males. Of the 386 respondents, nurses constituted the majority of the respondents (293; 75.9%), and there were 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
128
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 11 publications
(11 reference statements)
15
128
1
2
Order By: Relevance
“…Female students of health and non-health majors were reported to have more anxiety, while no gender difference was found in another study of medical students, with both studies describing undergraduate students during or after the SARS epidemic [15,16]. In another study about MERS-CoV outbreak perceptions of risk and stress evaluation in nurses, females were also found to have significantly more fear of contracting the virus compared to males [17]. In our study, the stress score was 5.14 ± 1.72 of junior medical students were more worried, but it was not statistically significant.…”
Section: Discussionmentioning
confidence: 89%
“…Female students of health and non-health majors were reported to have more anxiety, while no gender difference was found in another study of medical students, with both studies describing undergraduate students during or after the SARS epidemic [15,16]. In another study about MERS-CoV outbreak perceptions of risk and stress evaluation in nurses, females were also found to have significantly more fear of contracting the virus compared to males [17]. In our study, the stress score was 5.14 ± 1.72 of junior medical students were more worried, but it was not statistically significant.…”
Section: Discussionmentioning
confidence: 89%
“…See: http://creativecommons.org/licenses/by-nc/4.0/. Box 3: Recommendations to deal with psychological problems in healthcare workers in novel outbreaks Individual factors • Staff "buddy" system to support personal precautionary measures 40 • Encouragement among peers 43 • Sufficient rest and time off 35 43 • Opportunities for reflection on the effects of stress 56 66 • Increased support from family and friends 16 17 Service factors • Communication and training ○ Clear communication with staff 12 ○ Redesigning nursing care procedures that pose high risks for spread of infections 34 67 ○ Improving safety such as a better ventilation system or constructing or negative pressure rooms to isolate patients 34 67 ○ Reducing the density of patients on wards 34 67 • Psychological ○ Recognition of staff efforts 13 ○ Training to deal with identification of and responses to psychological problems 22 28 ○ Minimising time in quarantine 22 33 38 ○ Access to psychological interventions 16 12 13 40 43 ○ Avoidance of compulsory assignment to caring for patients with coronavirus 35 55 ○ Rearranging hospital infrastructure, such as redeployment of wards and human resources 34 67 ○ Availability of hospital security to help deal with uncooperative patients 22 • Personal support ○ Guaranteed food and daily living supplies 13 22 43 ○ Alternative accommodation for staff who are concerned about infecting their families 22 33 67 ○ Video facilities for staff to keep in contact with families and alleviate their concerns 22 Societal factors ○ Attention to media portrayal of healthcare workers 66 ○ Minimisation of stigma and discrimination 15…”
Section: Data Sharing: No Additional Data Availablementioning
confidence: 99%
“…Along with high risk of being infected, studies reported that health care personnel experienced occupational risks, distress, and the fear of contacting and transmitting the disease during epidemics of H1N1, severe acute respiratory syndrome (SARS), and Ebola virus (Bukhari et al, 2016;Chou et al, 2010;Corley, Hammond, & Fraser, 2010;Koh, Hegney, & Drury, 2012;Speroni, Seibert, & Mallinson, 2015).…”
Section: Introductionmentioning
confidence: 99%